(3GSGSjGJ GOGQI efXeGJ GdGYeGd (B:s (3GdhXGFa hGdeeGQSGJ GdGOGQjI (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2006)
(3eaghe GdGOGQI h GgejJgG h JWhQ GdacQ GdGOGQj GVGaI Gdi GdeOQGA HGdefXeGJ h GJNGP GdbQGQGJ h Md GdeTcdGJ h cPG GdGSGdjH GdMOjKI aj GJNGP GdbQGQGJ h cPG GdJNWjW h GdJfXje h GdSdWI aj GdJfXje h GdGTcGd GdJfXjejI h GdJfSjb h GdGJUGd h GNjQG GdQbGHI(B.s
(3eQGLY U(B.345s
Keywords: (3GJNGP GdbQGQGJs; (3GdGOGQIs; (3GdhXGFa GdGOGQjIs